Emotional Intelligence among Lithuanian and Latvian Student Athletes - Romualdas Malinauskas; Zermena Vazne (Lithuanian Sports University, 2018)
Background. This article deals with the issue of the manifestation of emotional intelligence in Lithuanian and Latvian student athletes. Emotional intelligence has been suggested as providing a new perspective on how emotional competencies necessary for performance in today's workplace among would-be physical educators might be more effective and better understood. Hence, the following research question is raised: does the emotional intelligence of  Lithuanian  student  athletes  differ  from  that  of  Latvian  student  athletes? We  hypothesized  that  the  emotional intelligence of Lithuanian student athletes differs from that of Latvian student athletes. Research aim was to reveal the manifestation of emotional intelligence in Lithuanian and Latvian student athletes. Methods. The independent random sample consisted of 227 student athletes from the Latvian Academy of Sports Education and 214 student athletes from the Lithuanian Sports University. Schutte Self-Report Inventory (SSRI) was employed. This instrument divides emotional intelligence into four separate components, namely: ability to use personal positive emotional experience (optimism), ability to assess and express emotions (appraisal), ability to understand and analyse emotions (social skills) and ability to manage emotions (utilization). Results. The analysis of the ability to use personal positive emotional experience resulted in the following averages: 51.48 ± 5.24 in case of the Lithuanian student athletes and 52.78 ± 6.33 in case of the Latvian student athletes. The application of the Student's t-test revealed a statistically significant difference in the ability of the Lithuanian  student  athletes  to  use  own  positive  emotional  experience  and  that  of  the  Latvian  student  athletes:   t (439) = 2.32; p < .005. Conclusions. The comparison of the components of emotional intelligence of Lithuanian and Latvian student athletes revealed that Latvian student athletes have better ability to use own positive emotional experience (optimism) (p < .05). No other statistically significant difference between Lithuanian and Latvian student athletes in terms of the components of emotional intelligence was observed. Keywords: emotional intelligence, emotions, student athletes.